Sibling Rivalry or Parental Negligence - Dr. Garima Chaudhary, (International Journal of Management Studies (IJMS), 2021)
The relation of a brothers and sisters is considered to be one of the most long lasting and beautiful of all. With the change in time, it has been re shaped and has formed altogether a new form which is comprises of jealousy, competition and comparison which creates sibling rivalry. The paper analyses the causes behind the sibling rivalry, the positive side of sibling rivalry and various techniques have been suggested in order to deal with sibling rivalry. If dealt nicely, the relationship of a sibling can be found beautiful and nurturing throughout the lifetime, both during childhood as well as during the time of maturity.